Repeat hepatectomy for liver metastases from bile duct neuroendocrine tumor: a case report - Mamiko Miyashita; Yoshihiro Ono; Manabu Takamatsu; Yosuke Inoue; Takafumi Sato; Hiromichi Ito; Yu Takahashi; Akio Saiura (Surgical Case Reports)
Abstract Background Primary neuroendocrine tumor (NET) originating from the extrahepatic bile duct is rare, although liver metastasis from gastroenteropancreatic NET is frequently observed. We herein report a case who successfully underwent repeat hepatectomy for liver metastases from bile duct NET grade 2 (G2). Case presentation A 75-year-old man presented with jaundice and was suspected of perihilar cholangiocarcinoma by computed tomography (CT) and magnetic resonance imaging (MRI). He underwent extended left hepatectomy, extrahepatic bile duct resection, and hepaticojejunostomy. Pathological findings showed a NET G2 of the biliary tract arising from the common bile duct. Two years and 11 months after surgery, a liver metastasis was detected and hepatectomy was performed. During the surgery, another liver metastasis was detected, and limited liver resection for the two lesions was performed. Pathological findings showed four liver metastases of NET G2. Five years and 4 months after the first surgery (2 years and 5 months after the second hepatectomy), four liver metastases were detected. Thereafter, he received somatostatin analogues for 1 year. Although the size of tumors increased slightly, the number did not change. He underwent limited liver resections and was diagnosed with 7 liver metastases of NET G2. Finally, another hepatectomy (fourth hepatectomy) was performed and long-term survival without recurrence was obtained for as long as 8 years after the first surgery. Conclusions Repeat hepatectomy is a good option to obtain long-term survival for liver metastases from bile duct NET G2 in select patients.